Community participation and sustainable forest management in Edo State (2011)
Contributions of forests to human well-being can only be sustained if the forests are sustained and local communities living within and around forest reserves have been identified to be central to meaningful planning for sustainable management of forest reserves. Studies in this direction are expected to contribute to poverty alleviation, environmental protection, and sustainable wood production this study is directed at ascertaining haw participatory approach involving local communities and other stakeholders can be used for sustainable management of forest reserves in Edo State. Stratified random sampling technique with a minimum of 30% sampling intensity was used to select 296 rural dwellers in the settlements within and around Ehor, Okomu, and Sakpoba forest reserves in the study area. Information was obtained on demographic and social status of the respondents, importance of the reserves to livelihoods, impressions about management system, forest resource use and willingness to participate in JFM using structured questionnaire, Rapid Rural Appraisal and Participatory Rural Appraisal techniques. Data obtained were subjected to descriptive and Chi-square test statistics at p = 0.05. None of the socio-economic characteristics of the respondents apart from religion (t = 2.39; P ≤ 0.02) in Okomu forest reserve significantly impacted their interest in forest conservation. However, ethnic background (t = 2.09), marital status (t = 2.22) and gender (t = -2.09) significantly (P ≤ 0.04) impacted interest in tree planting. Also, awareness of, and participation in local management activities were impacted by socio-economic status, most especially in Ehor and Okomu. Most of the respondents (85.14%) obtained produce from forest reserves , however, access to forest products was not significantly dependent on the income generating potential of the produce (X2= 9.35; df = 4). Some 14.43% of the respondents made an annual income of between N10,000:00 and N50, 000 while 57.5% of other stakeholders made between N1.5 and 3.5 million per annum. Conflict with forest officials is significantly (P ≤ 0.05) dependent on access to forest products (X2 = 70.44; df = 4) while perception of forest reserve law enforcement is not significantly dependent on access to forest produce. (X2 = 9.01; df = 4). Attitude of forest officials to forest law enforcement is a constraint to income generating activities in the study area. There exists no significant linear relationship between the willingness to participate in forest management and the identified socio-economic characteristics of rural dwellers in Okomu (F = 0.82), Sakpoba (F = 0.27) and Ehor (0.35) forest reserves. Also, apart from religion (t = 2.07) in Okomu forest reserve, none of the socio-economic attributes of rural dwellers had significant linear relationship with their opinion on JFM affecting livelihood (t = 2.07).